Penerapan Sistem Informasi Akuntansi dalam Efektivitas Pelaksanaan Pengendalian Intern : Studi Kasus pada PT Astra Internasional - Djanegara, H. Moermahadi Soerja; Danusaputra, Yonathan (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The structure of selling system and procedure encompasses all policies and procedures determined by management to control selling, either by credit or cash, in suited number and to appropriate consumers. Its required of internal control to support the smoothness of selling system and procedure. PT Astra International-Daihatsu Sales Operation has owned a very good and proper selling accounting information system. It can be observed from the ability of PT Astra International-Daihatsu Sales Operation in increasing effectiveness in carrying out internal control of its selling. The internal control of selling embraces control environment, risk estimate, control activity, communication and information, and monitoring. It can be known from the fact that PT Astra International-Daihatsu Sales Operation has achieved three categories of goal of internal control, namely: (a) operation effectiveness and efficiency, (b) accounting data reliability and accuracy, and (c) adherence to the prevailing rules and law. Keywords: Accounting information system; Internal control of selling